2012
DOI: 10.1371/journal.pone.0037375
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia Infections in a General Hospital: Patient Characteristics, Antimicrobial Susceptibility, and Treatment Outcome

Abstract: Introduction Stenotrophomonas maltophilia is acquiring increasing importance as a nosocomial pathogen.MethodsWe retrospectively studied the characteristics and outcome of patients with any type of S. maltophilia infection at the University Hospital of Heraklion, Crete, Greece, between 1/2005–12/2010. S. maltophilia antimicrobial susceptibility was tested with the agar dilution method. Prognostic factors for all-cause in-hospital mortality were assessed with multivariate logistic regression.ResultsSixty-eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 37 publications
6
97
0
3
Order By: Relevance
“…The most effective antibiotics in vitro were tigecycline, colistin, levofloxacin, SXT, then ticaricillin-clavulunic and ceftazidime, which showed the highest sensitivity (62.5%) among the β-lactams used in this study. Similar results were obtained by Samonis et al (16) who reported that colistin and tigecycline could be considered as new therapeutic options against S. maltophilia infections. This is also in line with Zhanel et al (20) who stated that tigecycline displayed good in vitro activity against MDR isolates of S. maltophilia.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The most effective antibiotics in vitro were tigecycline, colistin, levofloxacin, SXT, then ticaricillin-clavulunic and ceftazidime, which showed the highest sensitivity (62.5%) among the β-lactams used in this study. Similar results were obtained by Samonis et al (16) who reported that colistin and tigecycline could be considered as new therapeutic options against S. maltophilia infections. This is also in line with Zhanel et al (20) who stated that tigecycline displayed good in vitro activity against MDR isolates of S. maltophilia.…”
Section: Resultssupporting
confidence: 88%
“…The association of sul genes and Integron 1 with resistance to SXT had a statistically significant difference (x 2 =23.9, P<0.0001) (Table 3 & Fig.1). (19) reported that 59% of S. were from respiratory specimen (16.22%), blood (14.87%) and urine Samonis et al (16) reported that infection associated with S. maltophilia tractinfection (54.4%) followed infections (16.2%), skin and soft (10%) and lastly urinary tract infection…”
Section: Resultsmentioning
confidence: 99%
“…TMP/SMX, ticarcillin-clavulanate, fluoroquinolone, colistin, and tigecycline are agents that show consistent therapeutic activity against SM. However, because resistant strains of SM have increased, combination regimens are recommended [5]. We have treated patients with a combination of TMP/SMX and fluoroquinolone with successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It general, S. maltophilia is unable to infect human hosts because it is unable to easily bypass the basic immune defenses (3) . In spite of this, S. maltophilia has been gaining increased attention as an emerging pathogen in the past two decades for a number of reasons, especially in hospital settings (2,6,8,10) . S. maltophilia has been shown to be highly resistant to a suite of antibiotics, including quinones, β-lactams (carbapenems, penicillins, cephalosporins) and aminoglycosides (3) .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is now commonly found on a variety of common medical equipment, including catheters, endotracheal tubes, and other indwelling-lines that aid in the bacteria's transmission into its host (3) . Once entry into the a host has been established, S. maltophilia infection primarily results in pneumonia, but bloodstream infections (septicemia), infection on the skin and soft tissues, urinary tract infections, intraabdominal infections, and even ocular infections can also occur (8) .…”
Section: Introductionmentioning
confidence: 99%